HIV Disease Progression Among Antiretroviral Therapy Patients in Zimbabwe: A Multistate Markov Model - Matsena Zingoni, Zvifadzo; Chirwa, Tobias F.; Todd, Jim; Musenge, Eustasius (Frontiers in Public Health, 2019)
Background: Antiretroviral therapy (ART) impact has prolonged survival of people living with HIV. We evaluated HIV disease progression among ART patients using routinely collected patient-level data between 2004 and 2017 in Zimbabwe. Methods: We partitioned HIV disease progression into four transient CD4 cell counts states: State 1(CD4≥500cells/uL), State 2(350cells/uL≤CD4<500cells/uL), State 3(200cells/uL≤CD4 <350cells/uL), State 4(CD4<200cells/uL) and the absorbing state death (State 5). We proposed a semi-parametric time homogeneous Multistate Markov model to estimate bidirectional transition rates. Covariate effects (age, gender, ART initiation period and health facility level) on the transition rates were assessed. Results: We analyzed 204,289 clinic visits by 63,422 patients. There were 24,325 (38.4%) patients in State 4(CD4<200) at ART initiation and 7,995(12.6%) deaths occurred by December 2017. The overall mortality rate was 3.9 per 100 person-years. The highest mortality rate of 5.7 per 100 person-years (4,541 deaths) was from State 4(CD4<200) compared to other states. Mortality rates decreased with increase in time since ART initiation. Health facility type was the strongest predictor for immune recovery. Provincial or central hospital patients showed a diminishing dose-response effect on immune recovery by state from a hazard ratio(HR) of 8.30 (95%CI: 6.64-10.36) [State 4 to 3] to HR 3.12(95%CI: 2.54-4.36) [State 2 to 1] compared to primary health care (PHC) facilities. Immune system for males was more likely to deteriorate, and they had a 32% increased mortality risk [HR 1.32; 95%CI: 1.23-1.42] compared to females. Elderly patients (45+ years) were more likely to immune deteriorate compared to 25-34 years age-group: HR 1.35; 95%CI: 1.18-1.54, HR 1.56; 95%CI: 1.34-1.81 and HR 1.53; 95%CI: 1.32-1.79 for State 1 to 2, State 2 to 3 and State 3 to 4, respectively. Conclusion: Immune recovery was pronounced among provincial or central hospitals. Male patients with lower CD4 cell counts were at a higher risk of immune deterioration and mortality while elderly patients were more likely to immune deteriorate. Early therapeutic interventions when the immune system is relatively stable across gender and age may contain mortality and increase survival outcomes. Interventions which strengthen ART services in PHC facilities are essential.